Kidney Transplantation: A Simulation Model for Examining Demand and Supply - Ruth, R. Jean; Wyszewianski, Leon; Herline, Gary (Management Science, 1985)
In most regions of the United States there is a serious imbalance between the number of kidneys donated for transplantation and the number of persons wishing to receive a transplant. This not only affects the quality of life of those unable to obtain a transplant, but it also has important repercussions on the large and rapidly growing federal expenditures for the treatment of end-stage renal disease by transplantation and dialysis. A simulation model was constructed to assess the impact that changes in the number of cadaveric kidneys donated in Michigan would have on the waiting list of potential kidney transplant recipients in the state. The model represents the process of matching donated kidneys to people on the waiting list, taking into account the compatibility of the donor with the potential recipient's blood type and the tissue compatibility of the recipient to the donor as estimated by cytotoxicity. We describe the structure and data needs of the model, and we discuss the results obtained for Michigan. It was found that, under the current conditions, the waiting list would continue to grow rapidly. The number of donors needed to compensate for this growth would have to be disproportionately large: as the number of donations increases the effect of each donation in reducing the waiting list is less. The approach is applicable to other regions and it should also be adaptable to other types of organ transplants that require tissue compatibility, once such transplants become common enough to warrant regional coordination of the matching of recipients with donors.